Adaptation and achievement of Southern Patani students of Thailand in West Sumatera - Habalee Duereh; Azmi Fitrisia; Adri Febrianto (SCHOULID: Indonesian Journal of School Counseling, 2025)
This study explores the adaptation and academic achievement of Southern Patani Thai students in West Sumatra. These students face various challenges, including language barriers, differences in teaching methods, and limited access to academic facilities. Using qualitative methods—observation, in-depth interviews, and documentation—the study found that students often struggle with understanding lectures and adjusting to academic expectations. However, strong motivation, support from lecturers and peers, and active involvement in student communities significantly help them adapt. Academic performance among students varies based on how effectively they overcome these challenges and the level of support received. Some achieve well due to effective strategies and support, while others face ongoing difficulties. The findings highlight the need for structured support programs to assist international students in navigating academic and social environments, helping them reach their full potential during their studies in West Sumatra